Molecular markers of resistance to amodiaquine plus sulfadoxine-pyrimethamine in an area with seasonal malaria chemoprevention in south central Niger - Grais, R; Laminou, I; Woi-Messe, L; Makarimi, R; Bouriema, S; Langendorf, C; Amambua-Ngwa, A; D'Alessandro, U; Guérin, P; Fandeur, T; Sibley, C (BioMed Central, 2018)
Background In Niger, malaria transmission is markedly seasonal with most of the disease burden occurring in children during the rainy season. Seasonal malaria chemoprevention (SMC) with amodiaquine plus sulfadoxine– pyrimethamine (AQ + SP) is recommended in the country to be administered monthly just before and during the rainy season. Moreover, clinical decisions on use of SP for intermittent preventive treatment in pregnancy (IPTp) now depend upon the validated molecular markers for SP resistance in Plasmodium falciparum observed in the local parasite population. However, little is known about molecular markers of resistance for either SP or AQ in the south of Niger. To address this question, clinical samples which met clinical and biological criteria, were collected in Gabi, Madarounfa district, Maradi region, Niger in 2011–2012 (before SMC implementation). Molecular markers of resistance to pyrimethamine (pfdhfr), sulfadoxine (pfdhps) and amodiaquine (pfmdr1) were assessed by DNA sequencing. Results Prior to SMC implementation, the samples showed a high proportion of clinical samples that carried the pfdhfr 51I/59R/108N haplotype associated with resistance to pyrimethamine and pfdhps 436A/F/H and 437G mutations associated with reduced susceptibility to sulfadoxine. In contrast mutations in codons 581G, and 613S in the pfdhps gene, and in pfmdr1, 86Y, 184Y, 1042D and 1246Y associated with resistance to amodiaquine, were less frequently observed. Importantly, pfdhfr I164L and pfdhps K540E mutations shown to be the most clinically relevant markers for high level clinical resistance to SP were not detected in Gabi. Conclusion Although parasites with genotypes associated with the highest levels of resistance to AQ + SP are not yet common in this setting, their importance for deployment of SMC and IPTp dictates that monitoring of these markers of resistance should accompany these interventions. This study also highlights the parasite heterogeneity within a small spatial area and the need to use caution when extrapolating results from surveys of molecular markers of resistance in a single site to inform regional policy decisions.